The role of B-type natriuretic peptide in diagnosing acute decompensated heart failure in chronic kidney disease patients - Kadri, Amer N. (2018)
Introduction: Chronic kidney disease (CKD) and congestive heart failure (CHF) patients have higher serum B-type natriuretic peptide (BNP), which alters the test interpretation. We aim to define BNP cutoff levels to diagnose acute decompensated heart failure (ADHF) in CKD according to CHF subtype: heart failure with preserved ejection fraction (HFpEF) and heart failure with reduced ejection fraction (HFrEF). Material and methods: We reviewed 1,437 charts of consecutive patients who were admitted for dyspnea. We excluded patients with normal kidney function, without measured BNP, echocardiography, or history of CHF. BNP cutoff values to diagnose ADHF for CKD stages according to CHF subtype were obtained for the highest pair of sensitivity (Sn) and specificity (Sp). We calculated positive and negative likelihood ratios (LR+ and LR–, respectively), and diagnostic odds ratios (DOR), as well as the area under the receiver operating characteristic curves (AUC) for BNP. Results: We evaluated a cohort of 348 consecutive patients: 152 had ADHF, and 196 had stable CHF. In those with HFpEF with CKD stages 3–4, BNP < 155 pg/ml rules out ADHF (Sn90%, LR– = 0.26 and DOR = 5.75), and BNP > 670 pg/ml rules in ADHF (Sp90%, LR+ = 4 and DOR = 6), with an AUC = 0.79 (95% CI: 0.71–0.87). In contrast, in those with HFrEF with CKD stages 3–4, BNP < 412.5 pg/ml rules out ADHF (Sn90%, LR– = 0.19 and DOR = 9.37), and BNP > 1166.5 pg/ml rules in ADHF (Sp87%, LR+ = 3.9 and DOR = 6.97) with an AUC = 0.78 (95% CI: 0.69–0.86). All LRs and DOR were statistically significant. Conclusions: BNP cutoff values for the diagnosis of ADHF in HFrEF were higher than those in HFpEF across CKD stages 3–4, with moderate discriminatory diagnostic ability.